Reaction to aquatic medium during the infancy - Vallet, J.; Magnin, C. (First International Symposium on "Biomechanics and Swimming, Waterpolo and Diving", 14-16 September 1970. Proceedings, 1971)
History: - origin of the experience - his evolution binded to a revision of objectives of the practice and organisation - the last step: - refinement of the observation - tentative of programmation of situations who permit to the child to take his self government in water